A Comparison between the Mood Analyses of the Two Talk Shows with Different Social Statues - Ae Mon Kyaw (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2019)
Language cannot be separated from the social context and culture. In everyday communication, people act and react differently according to the interactants, the topics and the ways of communication. This study, therefore, analyzed the Talk Shows with different power statuses- Ellen with Vice President Joe Biden and Ellen with a volunteering Teacher. The analysis is carried out with the use of Halliday’s Mood analysis revised by M. Matthiessen (2014) and Eggin (2004). The present study will compare Ellen’s use of Mood structures and the functions in interacting with different social beings. It is found out that in the talk with Vice President, Ellen uses questions most (28.37%), followed by the second most frequently used statements (20%) while in the talk with Teacher, Ellen prioritized statements (43%) more than questions (14%). On the other hand, she does not enjoy any Commands (0%) in the talk with the Vice President but to the Teacher (18%). The result shows that more powerful participant has the tendency to answer the questions rather than asking questions, unlike Fairclough’s (2001) finding.